Evaluation of Compliance of Urban Land Use Zones to Integrated Land Use Plan in Meru Municipality, Meru County, Kenya - Riungu, James Muthomi; Kathuri, Muses Njeru (PT. Pubsains Nur Cendekia, 2024)
Urbanization is supposed to follow a guided land use plan. However, in most of the towns in Kenya, Meru municipality included, this has not been the case. This can be linked to violation of land use plan regulations. This study evaluated the land use zones' compliance level with integrated land use plans in Meru municipality. The study sought to establish the level of compliance of various urban land use zones to the integrated Land use plan of Meru municipality. A sample of 389 residents from a population of 88,871 was selected using Krejcie & Morgan (1970) formulae. Questionnaires, interviews, remote sensing, and observations were used to collect data from developers and key informants. The study found that the average compliance levels of the five land zones were as follows: recreational/ Conservation zone (83.3%), commercial (75.8%), agricultural (52.8%), residential (50.1%), and compliance of industrial zone 44.8%. The study therefore recommended the following: land use plan implementation needs close monitoring; planning officials in Meru municipality need capacity building on evaluation and follow-up on land use plans.